Skier's posture estimation using real time kinematics GNSS measurements - Nemec, B.; Petriè, T.; Supej, M. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
High precision Global Navigation Satellite System (GNSS) measurements are becoming more and more popular also in alpine skiing due to relatively undemanding setup and excellent performance. Unfortunately, GNSS basically provides only a single point measurement, where the antenna is placed, typically behind the skier`s neck. The key issue is how to estimate other even more relevant parameters, like center of mass (COM) trajectories, skis trajectories and skier's pose.